2017
DOI: 10.1038/ncomms14888
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas T6SS effector recruits PQS-containing outer membrane vesicles for iron acquisition

Abstract: Iron sequestration by host proteins contributes to the defence against bacterial pathogens, which need iron for their metabolism and virulence. A Pseudomonas aeruginosa mutant lacking all three known iron acquisition systems retains the ability to grow in media containing iron chelators, suggesting the presence of additional pathways involved in iron uptake. Here we screen P. aeruginosa mutants defective in growth in iron-depleted media and find that gene PA2374, proximal to the type VI secretion system H3 (H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
297
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(307 citation statements)
references
References 68 publications
7
297
0
3
Order By: Relevance
“…These multi‐component secretion machines can mediate contact dependent killing of prokaryotic as well as eukaryotic cells (Hood et al ., ; Silverman et al ., ; Böck et al ., ). Besides killing adjacent bacterial cells, recent investigations have revealed that T6SS play multiple non‐killing functions, e.g., mediating intracellular pH homeostasis (Zhang et al ., ), Zn 2+ transport (Wang et al ., ), manganese/iron scavenging and resistance to reactive oxygen species (Lin et al ., ; Si et al ., ; Wan et al ., ), facilitating bacterial stress adaptation to changing environmental conditions. Most of the killing and non‐killing functions of T6SS are mediated by specific effector proteins propelled outside of bacterial cells and into adjacent recipient cells through the action of contractile T6SS (Basler and Mekalanos, ).…”
Section: Introductionmentioning
confidence: 99%
“…These multi‐component secretion machines can mediate contact dependent killing of prokaryotic as well as eukaryotic cells (Hood et al ., ; Silverman et al ., ; Böck et al ., ). Besides killing adjacent bacterial cells, recent investigations have revealed that T6SS play multiple non‐killing functions, e.g., mediating intracellular pH homeostasis (Zhang et al ., ), Zn 2+ transport (Wang et al ., ), manganese/iron scavenging and resistance to reactive oxygen species (Lin et al ., ; Si et al ., ; Wan et al ., ), facilitating bacterial stress adaptation to changing environmental conditions. Most of the killing and non‐killing functions of T6SS are mediated by specific effector proteins propelled outside of bacterial cells and into adjacent recipient cells through the action of contractile T6SS (Basler and Mekalanos, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PQS signal molecules in OMV can hijack iron ions from the extracellular medium via the OMV-associated metal-binding protein TseF, secreted by the type 6 secretion system (T6SS). The delivery of PQS-iron complexes into recipient bacterial cells goes through interaction between the TseF (T6SS effector for iron uptake), ferric pyochelin receptor FtpA, and porin OprF [62, 64]. In parallel, QS enables differential regulation of the expression of genes at the loci of T6SS [65].…”
Section: Qs-regulated Factors That Impact P Aeruginosa Communities Amentioning
confidence: 99%
“…For instance, P. aeruginosa AHL with a short fatty acid chain containing 4–6 carbons are freely diffusible across the membrane, in contrast to those with a long acyl chain, 3O-C 12 -HSL, and PQS, due to the larger size and hydrophobic nature of the latter [91]. The PQS transport across the bacterial membrane is facilitated by membrane transporters and bacterial OMV that also contain other bacterial products [64]. The active traffic of 3O-C 12 -HSL across cell membranes is driven by members of a large family of proteins, called the ATP binding cassette (ABC) transporter.…”
Section: Traffic and Human Targets For P Aeruginosa 3o-c12-hslmentioning
confidence: 99%
“…Proteomic studies of OMVs from diverse bacterial species have revealed a number of metal-ion-binding proteins (47). Recent work by Lin et al (48) elucidated a mechanism that enables Pseudomonas aeruginosa to access metal-rich OMVs via a type VI secretion system (T6SS). TseF is secreted by the T6SS and associates with the Pseudomonas quinolone signal (PQS) as well as P. aeruginosa receptors OprF and FptA.…”
Section: Being a Good Neighbor: Benefits Provided By Omvsmentioning
confidence: 99%